Three new troglobitic species of Pseudochthonius Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from northeastern Brazil - Prado, Guilherme C.; Ferreira, Rodrigo L. (Zootaxa, 2023)
Three new pseudoscorpion species, Pseudochthonius pali sp. nov., Pseudochthonius diamachi sp. nov., and Pseudochthonius koinopoliteia sp. nov., are herein described from caves of Bahia state, Brazil. They can be distinguished from congeners mainly by the absence of eyes or eyespots, chelal and cheliceral dentition, coxal chaetotaxy and body size. Some ecological remarks on each species, possible threats, recommendations for future research and a key to the Pseudochthonius species from Brazil are provided.